Character: Samuel Peláez Vélez (2009)
Samuel always brings may questions to Conversations with Professors, the final moment of workshops at EAFIT Children's University. It is possible that his mates in group 3 and the other participants will never forget his interventions. He considers that he is imaginative, curious and cheerful. He likes to draw, paint, and write, but especially to help people. In this interview Samuel answered some questions about him.